Ответы и объяснения

2013-07-02T20:04:54+00:00

х=2-у  подставляем во второевместо х получим (2-у)^2-у=4  решаем  4-4у+у^2-у=4

5у+у^2=0  у(-5+у)=0  у=0   х=2  Ответ:х=2    у=0

- 5+у=0

у=5 тогда х=2-5  х=-3 получатся тогда такой ответ-----х=2 у=0  и х=-3 у=5

 

 

 

  • AlbuRin
  • светило науки
2013-07-03T01:41:10+00:00

{x+y=2      {y=2-x                                                                                у_1 = 5     у_2 = 0

{x^2-y=4   {x^2-2+x-4=0 ----> x^2+x-6=0  По  теореме Виета  х_1 = -3    х_2 = 2